2015
DOI: 10.1371/journal.pone.0118043
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Candidate Exonic Variants for Association to Alzheimer Disease in the Amish

Abstract: Alzheimer disease (AD) is the most common cause of dementia. As with many complex diseases, the identified variants do not explain the total expected genetic risk that is based on heritability estimates for AD. Isolated founder populations, such as the Amish, are advantageous for genetic studies as they overcome heterogeneity limitations associated with complex population studies. We determined that Amish AD cases harbored a significantly higher burden of the known risk alleles compared to Amish cognitively no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
4
22
0
Order By: Relevance
“…Lavorgna and Harhaj found that STAMBPL1 regulated NF-κB activation in neuroinflammation process [33]. It is worth mentioning that the missense mutation of STAMBPL1 has been found in AD in the Amish [7]. In this study, we also found the relationship between STAMBPL1 and AD, which further suggested that STAMBPL1 may be a crucial factor in the pathology of AD.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Lavorgna and Harhaj found that STAMBPL1 regulated NF-κB activation in neuroinflammation process [33]. It is worth mentioning that the missense mutation of STAMBPL1 has been found in AD in the Amish [7]. In this study, we also found the relationship between STAMBPL1 and AD, which further suggested that STAMBPL1 may be a crucial factor in the pathology of AD.…”
Section: Discussionsupporting
confidence: 75%
“…The risk of genetic component of AD has been evidenced by the increased risk of AD among first-degree relatives of affected patients [6]. There are several other risk factors associated with AD, such as aging, age, activity, lifestyle, education, family history, and atherosclerosis [7]. Along with the progressively incapacitating, AD can linger many years.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 shows that the top 10 gene-level findings identified by MGAS, where APOE ( p = 2.77E-08), TOMM40 ( p = 3.49E-08), and APOC1 ( p = 2.09E-06) are the well-known AD risk regions. LAMA1 ( p = 3.79E-05) was reported to encode the laminin alpha subunit associated with late onset AD in the Amish [ 22 ]. HSD17B7P2 ( p = 8.40E-05) was reported to play an important role in brain development [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence that cerebrovascular dysregulation plays a role in neurodegeneration and AD [47] . A recent whole-exome sequencing study in the Amish population identified a synonymous variant in LAMA1, rs73938538 [48] . PTPRM encodes protein tyrosine phosphatase, receptor type M, a member of the protein tyrosine phosphatase (PTP) family.…”
Section: Discussionmentioning
confidence: 99%